A study on the drying behaviour of a local variety (Lalpakri) of potato (Solanum tuberosum L.) - Sarker, Ayesha; Islam, MN; Shaheb, MR (Bangladesh Journal of Agricultural Research, 2012)
The study was carried out in the laboratory of the Department of Food Technology and Rural Industries, Bangladesh Agricultural University, Mymensingh during 2008-09 to analyze the drying behaviour of potato (var. Lalpakri) at variable air dry bulb temperature using a mechanical dryer. Fresh potatoes with 3, 5, 7 mm slices were used as raw materials for drying. The experiment showed that drying rate constant decreases with the increases in thickness and increasing loading density of potato slice, the rate of drying decreases but drying rate constant does not decrease proportionately. From the relationship between drying rate constant and thickness, the value of exponent n of the power law equations was recorded 0.4586. It was observed that higher temperatures gave faster drying rate. From the exponential relationship between diffusion co-efficient (De) versus inverse absolute temperature (Tabs -1), activation energy (Ea) for diffusion of water from local variety of potato (var. Lalpakri) was found to be 5.60 Kcal/gm-mole. Bangladesh J. Agril. Res. 37(3): 505-514, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12127